The influence of economic growth, population, and fossil fuel scarcity on energy investments - Enrica De Cian; Fabio Sferra; Massimo Tavoni (Fondazione Eni Enrico Mattei (FEEM), 2013)
This paper examines the dynamics of energy investments and clean energy Research and Development (R&D) using a scenario-based modeling approach. Starting from the global scenarios proposed in the RoSE model ensemble experiment, we analyze the dynamics of investments under different assumptions regarding economic and population growth as well as availability of fossil fuel resources, in the absence of a climate policy. Our analysis indicates that economic growth and the speed of income convergence across countries matters for improvements in energy efficiency, both via dedicated R&D investments but mostly through capital-energy substitution. In contrast, fossil fuel prices, by changing the relative competitiveness of energy sources, create an economic opportunity for radical innovation in the energy sector. Indeed, our results suggest that fossil fuel availability is the key driver of investments in low carbon energy innovation. However, this innovation, by itself, is not sufficient to induce emission reductions compatible with climate stabilization objectives.
Keywords: O13; Q43; Q54; Q55; 330; Technological change and innovation; Energy investments; R&D Investments; Fossil fuel availability; Fossil fuel prices; Energy Intensity; Carbon Intensity